Namūzaj al Ta'līm al Tasyārukiy fi Ta'līm al Sharfi ( Dirāsah Hālah fi Mustawa al Rābi' Jami'ah al Islāmiyah al Hukūmiyah Padangsidimpuan - Nurfin Sihotang; Yunaldi Yunaldi (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan dan Bahasa Arab, 2022)
Participatory Learning Model in Sharaf Learning (case study in Semester IV of Padangsidimpuan State Islamic University) Sharaf's teaching is related to the teaching of Arabic, in the process of teaching many students face difficulties and problems. The formulation of this research is what is the problem with Sharaf's Teaching in Semester IV of the Arabic Language Teaching Department Level IV at the Padangsidimpuan State Islamic Institute? The purpose of this research is to show the problems of learning Sharaf in Semester IV of the Arabic Language Teaching Department Level IV, Padangsidimpuan State Islamic Institute. And the research method is a qualitative research with data collection technique based on the triangulation method. The result of this study is that the main problem in Sharaf's learning is in teaching word scales and word polishing containing tassydid letter, and including heterogeneous student school origins, as well as learning methods that are not diverse and participatory models of Sharaf's learning model and this is a model that is able to to improve Sharaf's learning. The conclusion of this research is that there are problems in the educational process and their solutions